The Effect of Online Social Proof Regarding Organic Food: Comments and Likes on Facebook - Hilverda, Femke; Kuttschreuter, Margôt; Giebels, Ellen (Frontiers in Communication, 2018)
Social media created a new information environment (e.g. Rutsaert et al., 2013b). Among social media channels, Facebook is the most popular one (Cheung et al., 2011). Using Facebook people can exchange information rapidly with others. Consumers can post a statement or message on Facebook (a post), respond to these posts (the comments) and indicate that they agree with the post and/or comment by using the “thumb up” symbol (the likes). Both comments and likes are cues of social proof, e.g. the viewpoints of others. We investigated how social proof in an online environment impacts reactions towards organic foods in two experimental studies. In study 1, using a representative sample of Dutch internet users (n=124), we manipulated comment valence (positive vs negative) and reinforcement (number of likes: high vs low) on a fictitious Facebook page that included four comments. Consumers’ perceptions, feelings and behavior, such as risk perception, emotions and intended purchasing behavior, were measured. Comment evaluation was used as a moderator. In study 2 (n=88) a full Facebook page, with mixed valence statements, was shown; either the positive or negative statements were reinforced by likes. Results of study 1 showed that the way respondents evaluated the comments in terms of usefulness affected benefit perception and the motivation to find information. Moreover, the interaction between valence and comment evaluation was significant for all dependent variables. That is, the predicted effect of social proof only occurred when the comments were perceived as useful. The number of likes did not have an effect. Results of study 2 where participants watched a full Facebook page with mixed valence comments, showed that the number of likes had an effect on consumers’ reactions, specifically on negative emotions and willingness to pay. This research provides new insights in the effects of explicit as well as implicit online social proof on attitudes towards a positively evaluated topic, namely organic food.